2017
DOI: 10.1371/journal.pone.0184937
|View full text |Cite
|
Sign up to set email alerts
|

KRAS and BRAF somatic mutations in colonic polyps and the risk of metachronous neoplasia

Abstract: Background & aimsHigh-risk features of colonic polyps are based on size, number, and pathologic characteristics. Surveillance colonoscopy is often recommended according to these findings. This study aimed to determine whether the molecular characteristics of polyps might provide information about the risk of metachronous advanced neoplasia.MethodologyWe retrospectively included 308 patients with colonic polyps. A total of 995 polyps were collected and tested for somatic BRAF and KRAS mutations. Patients were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 47 publications
3
16
0
1
Order By: Relevance
“…Regarding macroscopic morphology, an association between a flat appearance and BRAF mutations has been reported . Such an association would be consistent with the higher BRAF mutation rates in SSA (which is sessile by definition) than TSA (which is typically pedunculated) .…”
Section: Discussionsupporting
confidence: 65%
“…Regarding macroscopic morphology, an association between a flat appearance and BRAF mutations has been reported . Such an association would be consistent with the higher BRAF mutation rates in SSA (which is sessile by definition) than TSA (which is typically pedunculated) .…”
Section: Discussionsupporting
confidence: 65%
“…From a biological perspective, cooccurrence of driver alterations clearly does occur [17,18,19,20], and appears to be a requirement for carcinogenesis, as evidenced by the insufficiency of BRAF and RAS hotspot mutations to transform benign colon polyps and nevi into invasive carcinoma [21,22]. However, statistical approaches to identifying cooccurrence have given mixed results.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have investigated the role of molecular markers in polyps for predicting the development of metachronous lesions, especially advanced adenomas, revealing an increased MACL risk in patients with KRAS-mutated polyps at baseline [ 5 ]. Concerning serrated lesions, a recent study has found no association between BRAF mutations or CIMP status in polyps at baseline and metachronous advanced lesions [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…To date, few studies have investigated the relationship between molecular markers and risk of developing metachronous neoplasia at follow-up. Some prior studies demonstrate that somatic mutation in KRAS ( K irsten RA t S arcoma virus) gene may predict metachronous advanced colorectal lesions (MACLs) during colonoscopic surveillance [ 5 ]. Additionally, studies applying the consensus molecular subtypes (CMSs) of CRC to polyps have indicated that certain genetic anomalies may be markers of future CRC risk [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%